Does release of antimicrobial agents from impregnated external ventricular drainage catheters affect the diagnosis of ventriculitis? - Bayston, Roger; Ashraf, Waheed; Ortori, Catherine (American Association of Neurological Surgeons, 2015)
OBJECT